Anti-condensation heat-preservation super-hydrophobic aerogel coating, preparation method thereof and application in industrial thermal equipment

CN122587590BActive Publication Date: 2026-10-27DEQING YANGTAI BUILDING MATERIAL
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611082157.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-21
Publication Date
2026-10-27
Estimated Expiration
2046-07-21

AI Technical Summary

Technical Problem

[0002]随着全球工业化进程的加速,工业热工装备如锅炉、蒸汽管道、换热器及高温反应器等在能源、化工、冶金等领域扮演着核心角色,这些设备在运行过程中面临热量散失导致的巨大能源浪费,以及因温差变化引发的表面冷凝现象的挑战,冷凝水不仅会腐蚀金属基材、滋生微生物,还会显著降低保温材料的隔热性能,严重缩短设备使用寿命并增加维护成本,因此,开发兼具高效保温与抗冷凝功能的防护涂层成为工业节能领域的重要研究方向

Benefits of technology

(1)本发明提供了一种抗冷凝保温型超疏水气凝胶涂料及其制备方法以及在工业热工装备中的应用,通过对二氧化硅气凝胶进行先接枝反应型硅烷、后接枝疏水型硅烷的分段改性处理,使得气凝胶颗粒表面同时具有了可与水性成膜树脂结合的反应性基团和用于降低表面能的疏水基团,克服了普通气凝胶粉体在水性涂料中与树脂相容性差且易形成界面微缺陷导致吸水的缺陷,使得气凝胶不仅在涂层中发挥导热系数低的隔热作用,还能够通过化学键与涂层骨架结合,在有效提升涂层抗粉化能力与耐冷热循环性能的同时,显著降低了湿态导热系数,确保了涂层在冷凝工况下的长期保温效果,优于仅简单复配疏水改性或反应改性气凝胶的现有技术。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122587590B_ABST
    Figure CN122587590B_ABST
Patent Text Reader

Abstract

The application discloses an anti-condensation heat-preservation type super-hydrophobic aerogel coating and a preparation method and application thereof in industrial thermal equipment, and comprises the following steps: segmentally modifying silica aerogel and reactive silane and hydrophobic silane in an alcohol-water mixed medium to obtain bifunctional modified aerogel containing resin binding groups and low surface energy groups; emulsifying phase change core material into droplets to obtain dew point response double-sided breathing microcapsules; grafting polysiloxane with the microcapsules; mixing water-based silicon modified film-forming resin, flaky shielding filler, flame-retardant filler, dispersant, defoaming agent, rheological modifier, film-forming aid and water to obtain a basic slurry; performing flow leveling, pre-curing and post-curing on the anti-condensation heat-preservation type super-hydrophobic aerogel coating, and enriching to obtain an anti-condensation heat-preservation type super-hydrophobic aerogel coating; and the wet-state thermal conductivity is significantly reduced, and the long-term heat preservation effect of the coating under the condensation working condition is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a superhydrophobic aerogel coating, and more particularly to an anti-condensation and heat-insulating superhydrophobic aerogel coating, its preparation method, and its application in industrial thermal equipment. Background Technology

[0002] With the acceleration of global industrialization, industrial thermal equipment such as boilers, steam pipelines, heat exchangers, and high-temperature reactors play a core role in energy, chemical, and metallurgical fields. During operation, these devices face the challenges of huge energy waste caused by heat loss and surface condensation caused by temperature differences. Condensate not only corrodes metal substrates and breeds microorganisms, but also significantly reduces the thermal insulation performance of insulation materials, severely shortens the service life of equipment, and increases maintenance costs. Therefore, developing protective coatings that combine efficient thermal insulation and anti-condensation functions has become an important research direction in the field of industrial energy conservation.

[0003] Traditional insulation materials such as rock wool, glass wool, and polyurethane foam are widely used, but they have inherent drawbacks such as high thermal conductivity, complex construction, and susceptibility to moisture absorption and aging. In recent years, aerogels, with their extremely low thermal conductivity (below 0.02 W / (m·K), high porosity, and lightweight properties, have been regarded as the next generation of ideal insulation materials. Dispersing aerogel powder in polymer resins to create composite coatings allows for convenient coating and integrated insulation of irregularly shaped surfaces, showing great potential in industrial thermal equipment. However, existing aerogel coatings have revealed serious performance bottlenecks in practical applications. Ordinary fumed silica or silica aerogel powders are rich in hydrophilic silanol groups on their surface. When blended with water-based acrylic, epoxy, or polyurethane resins, the significant difference in polarity makes it difficult to uniformly disperse the aerogel particles, leading to easy... More importantly, agglomeration and sedimentation occur because the aerogel particles lack effective chemical bonding or physical anchoring with the resin matrix. As a result, a large number of micro-scale interfacial voids and cracks form inside the cured coating. In a humid and hot environment, these micro-defects will rapidly adsorb and conduct moisture through capillary action. On the one hand, this causes the water absorption rate of the coating to increase sharply, destroying its original low thermal conductivity structure. On the other hand, the presence of moisture significantly increases the heat conduction path, leading to a significant decrease or even failure of thermal insulation performance. In addition, the volume expansion and reduced adhesion of the coating after water absorption further exacerbate the risk of interfacial debonding and cracking. Summary of the Invention

[0004] This invention overcomes the shortcomings of the prior art and provides a method for preparing an anti-condensation and heat-insulating superhydrophobic aerogel coating and its application in industrial thermal equipment.

[0005] To achieve the above objectives, the technical solution adopted by this invention is as follows: a method for preparing an anti-condensation and heat-insulating superhydrophobic aerogel coating, comprising the following steps: S1: Silica aerogel is modified in stages with reactive silane and hydrophobic silane in an alcohol-water mixed medium to obtain a bifunctional modified aerogel containing both resin-binding groups and low surface energy groups. S2: The phase change core material is emulsified into droplets, and an elastic intermediate layer, an inorganic nano-rough shell, and a bifacial outer surface with semi-through breathing channels are sequentially formed on the outside of the droplets to obtain dew point responsive bifacial breathing microcapsules. S3: Confined grafting of polysiloxanes with terminal hydroxyl, terminal epoxy, or terminal alkoxy groups to some bifunctional modified aerogels, silica sols, or dew-point responsive bifacial breathing microcapsules yields confined migration type low surface energy segment reservoirs. S4: A base slurry is obtained by mixing waterborne silicone-modified film-forming resin, sheet-like shielding filler, flame-retardant filler, dispersant, defoamer, rheology modifier, film-forming aid, and water. S5: Add the bifunctional modified aerogel, hollow heat-insulating microspheres and part of silica sol obtained in S1 to the base slurry obtained in S4, and mix them under low shear conditions to obtain aerogel heat-insulating slurry. S6: Add the dew-point responsive bifacial breathing microcapsules, hydrophobic nanoridge forming particles, and the confined migration type low surface energy chain segment reservoir obtained in S2 to the aerogel insulation slurry obtained in S5, adjust the pH value, wet film viscosity and solid content of the system, and obtain an anti-condensation heat-insulating superhydrophobic aerogel coating. S7: The anti-condensation and heat-insulating superhydrophobic aerogel coating obtained in S6 is applied to the outer surface of industrial thermal equipment, and leveling, pre-curing and post-curing are performed in sequence. This allows the dew point-responsive bifacial breathing microcapsules to accumulate on the side of the coating closest to the air, and together with the hydrophobic nanoridge particles and the confined migration low surface energy chain segment reservoir, they form a condensate droplet edge peeling structure, thus obtaining the anti-condensation and heat-insulating superhydrophobic aerogel coating.

[0006] In a preferred embodiment of the present invention, in S1, the silica aerogel has a particle size of 5-80 μm, a pore size of 10-100 nm, and an apparent density of 0.04-0.20 g / cm³. Reactive silanes include one or more of γ-glycidoxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane, methacryloyloxypropyltrimethoxysilane, or vinyltriethoxysilane; Hydrophobic silanes include one or more of octyltriethoxysilane, dodecyltrimethoxysilane, hexadecyltrimethoxysilane, methyltrimethoxysilane, or polydimethylsiloxane; The segmented modification involves first grafting reactive silanes at a pH of 4.0-6.0 and a temperature of 35-65℃ for 0.5-3 hours, and then grafting hydrophobic silanes at a pH of 7.0-9.5 and a temperature of 40-75℃ for 0.5-4 hours.

[0007] In a preferred embodiment of the present invention, in S2, the phase change core material includes one or more of C14-C22 n-alkanes, fatty acid esters, low-melting-point silicone wax or paraffin, and the phase change temperature of the phase change core material is 15-42℃. The dew-point responsive bifacial respiratory microcapsules have a particle size of 5-50 μm, a shell thickness of 0.2-3.0 μm, and a semi-perforated breathing channel pore size of 5-80 nm. The elastic interlayer includes one or more of polyurea, polyurethane, polysiloxane, or acrylate elastomer; Inorganic nano-rough shells include one or more of silica, silica sol condensate, silsesquioxane, nano-alumina, or sheet silicates. The bifacial outer surface includes a low surface energy side and a reactive bonding side. The low surface energy side contains one or more of polydimethylsiloxane segments, C8-C18 alkylsiloxane segments, or phenylsiloxane segments, while the reactive bonding side contains one or more of hydroxyl, amino, epoxy, carboxyl, or alkenyl groups.

[0008] In a preferred embodiment of the present invention, in S3, in the confined migration type low surface energy segment reservoir, one end of the polysiloxane segment forms a silicon-oxygen bond, hydrogen bond or covalent bond with the shell of a bifunctional modified aerogel, silica sol or dew point responsive bifacial breathing microcapsule, and the other end is a low surface energy segment that can be reoriented to the coating surface after heat treatment at 40-100°C. In confined migration type low surface energy chain segment storage, the mass of free polysiloxane accounts for 0-15% of the total polysiloxane mass.

[0009] In a preferred embodiment of the present invention, in S4 and S5, the waterborne silicone-modified film-forming resin includes one or more of the following: waterborne silicone-modified polyurethane emulsion, waterborne silicone-acrylic emulsion, waterborne siloxane-modified polyurethane-acrylic composite emulsion, or phosphate ester-modified acrylic emulsion. The sheet-like shielding filler includes one or more of mica, sericite, sheet-like silicate, hexagonal boron nitride, sheet-like alumina, or sheet-like ceramic filler; Flame-retardant fillers include one or more of aluminum hydroxide, magnesium hydroxide, expanded graphite, ammonium polyphosphate, melamine polyphosphate, or zinc borate; Hollow insulating microspheres include one or more of hollow glass microspheres, hollow ceramic microspheres, closed-cell expanded microspheres, or hollow silicate microspheres, with a particle size of 10-120 μm and an apparent density of 0.10-0.60 g / cm³. The low shear conditions are a rotation speed of 100-800 r / min and a mixing time of 5-40 min.

[0010] In a preferred embodiment of the present invention, in S6, the hydrophobic nanoridge forming particles include one or more of chain-like nano silica, fumed silica, hydrophobically modified silica sol, sheet-like nano silicates, nano alumina, or nano sericite, with a particle size or thickness of 10-500 nm. In S6, the pH value of the system is adjusted to 7.5-9.5, the wet film viscosity is adjusted to 3000-12000 mPa·s, and the solid content is adjusted to 45-78%.

[0011] In a preferred embodiment of the present invention, in step S7, the leveling temperature is 15-35°C and the time is 5-30 minutes; The pre-curing temperature is 40-80℃ and the time is 0.5-3h; the post-curing temperature is 60-110℃ and the time is 1-8h; the dry film thickness of the resulting anti-condensation and heat-insulating superhydrophobic aerogel coating is 0.5-5.0mm. The height of the dew-point responsive bifacial breathing microcapsules protruding from the coating surface is 10-45% of their particle size, and the spacing between adjacent dew-point responsive bifacial breathing microcapsules is 5-80 μm.

[0012] In a preferred embodiment of the present invention, the anti-condensation and heat-insulating superhydrophobic aerogel coating comprises, by weight, 18-45 parts of waterborne silicone-modified film-forming resin, 8-32 parts of bifunctional modified aerogel, 4-20 parts of hollow heat-insulating microspheres, 4-18 parts of dew-point responsive bifacial breathing microcapsules, 1-8 parts of hydrophobic nanoridge-forming particles, 2-14 parts of silica sol, 1-10 parts of sheet-like shielding filler, 5-25 parts of flame-retardant filler, 0.5-6 parts of confined migration type low surface energy chain segment reservoir, 0.2-2 parts of dispersant, 0.1-1 parts of defoamer, 0.2-3 parts of rheology modifier, 0.5-5 parts of film-forming aid, and 20-70 parts of water.

[0013] An anti-condensation and heat-insulating superhydrophobic aerogel coating, the coating formed after curing includes an anchoring shielding part near the substrate, an aerogel heat insulation part in the middle and a condensation repellency part near the air; the water contact angle of the coating is 150-168° and the roll-off angle is 1-10°.

[0014] Application of an anti-condensation and heat-insulating superhydrophobic aerogel coating in industrial thermal equipment, including cryogenic storage tanks, chilled water pipelines, heat exchanger shells, outer walls of reactor jackets, shutdown cooling sections of steam pipelines, compressed air aftercooling pipelines, heat pump equipment shells, cooling unit shells, or the outer surfaces of metal equipment that periodically cross dew point conditions.

[0015] This invention addresses the shortcomings of the prior art and has the following beneficial effects: (1) This invention provides an anti-condensation and heat-insulating superhydrophobic aerogel coating, its preparation method, and its application in industrial thermal equipment. By performing a segmented modification treatment on silica aerogel by first grafting reactive silane and then grafting hydrophobic silane, the surface of the aerogel particles simultaneously has reactive groups that can be combined with water-based film-forming resins and hydrophobic groups that can reduce surface energy. This overcomes the defects of ordinary aerogel powder in water-based coatings, such as poor compatibility with resins and easy formation of interfacial micro-defects leading to water absorption. This allows the aerogel to not only play a heat insulation role with low thermal conductivity in the coating, but also to be combined with the coating skeleton through chemical bonds. While effectively improving the coating's anti-chalking ability and resistance to thermal cycling, it significantly reduces the wet thermal conductivity, ensuring the long-term heat insulation effect of the coating under condensation conditions. This is superior to the existing technology of simply compounding hydrophobic modified or reactive modified aerogels.

[0016] (2) This invention provides an anti-condensation and heat-insulating superhydrophobic aerogel coating, its preparation method, and its application in industrial thermal equipment. By introducing a dew-point responsive bifacial breathing microcapsule, the microcapsule is made of phase change material as the core layer, and is wrapped with an elastic buffer intermediate layer, an inorganic nano-rough shell layer, and a bifacial outer surface with semi-through breathing channels. When the surface temperature of the industrial thermal equipment is close to the dew point, the internal phase change material can absorb and release heat to regulate the temperature drop rate of the coating surface, thereby delaying the formation of condensate droplets. At the same time, the semi-through breathing channels on the shell layer of the microcapsule can slowly release internal water vapor under normal conditions, while restricting liquid water from entering through the channels when approaching the dew point. This effectively solves the problem of moisture absorption failure of traditional superhydrophobic coatings caused by direct condensation and nucleation of water vapor inside the micro-nano structure, and realizes the active control and blocking of the condensation process.

[0017] (3) This invention provides an anti-condensation and heat-insulating superhydrophobic aerogel coating, its preparation method, and its application in industrial thermal equipment. By inducing microcapsules to be oriented and enriched in a controlled manner on the surface of the coating during the drying process of the wet film, the hydrophobic side faces the air interface, and the reactive side is firmly anchored to the resin skeleton. In conjunction with the hydrophobic nanoridge forming particles, a composite microstructure composed of compressible elastic micro-protrusions and discrete rigid nano-ridges is constructed on the surface of the coating. Through this structural design, the condensed droplets are supported by elastic micro-protrusions during the growth process and undergo local deformation under the action of micro-vibration, which promotes the preferential de-stacking and peeling of the droplet edges. This transforms the traditional overall rolling drainage mode of the coating into a synergistic drainage mode of edge de-stacking, local peeling, and overall sliding, which greatly reduces the adhesion and rolling angle of the droplets and overcomes the problem that existing superhydrophobic coatings are prone to droplet pinning in industrial vibration environments. Attached Figure Description

[0018] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort. Figure 1 This is a flowchart of a preferred embodiment of the present invention; Figure 2 These are electron micrographs of the product prepared according to a preferred embodiment of the present invention, wherein, Figure 2 Part (a) is an electron microscope schematic diagram of the bifunctional modified aerogel of a preferred embodiment of the present invention; Figure 2 Part (b) is an electron microscope schematic diagram of a dew-point responsive bifacial respiratory microcapsule according to a preferred embodiment of the present invention; Figure 2 Part (c) is an electron microscope schematic diagram of hydrophobic nanoridge-forming particles according to a preferred embodiment of the present invention; Figure 2 Part (d) is an electron microscope schematic diagram of the cross-section of the anti-condensation and heat-insulating superhydrophobic aerogel coating of a preferred embodiment of the present invention; Figure 3 This is a schematic diagram of the structure of the dew-point responsive bifacial respiratory microcapsule according to a preferred embodiment of the present invention; In the figure: 1. Phase change core material; 2. Elastic intermediate layer; 3. Inorganic nano-rough shell; 4. Low surface energy side; 5. Reactive bonding side; 6. Semi-through breathing channel. Detailed Implementation

[0019] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0020] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein. Therefore, the scope of protection of the invention is not limited to the specific embodiments disclosed below.

[0021] This invention relates to an anti-condensation, heat-insulating, superhydrophobic aerogel coating suitable for the outer surfaces of industrial thermal equipment. The outer surface refers to the outer wall surface of the equipment used for heat insulation, protection, and condensation suppression, excluding heat exchange working surfaces intended to improve heat exchange efficiency. During operation, shutdown, heating, or cooling of industrial thermal equipment, the temperature of its outer surface may approach or fall below the ambient dew point, making it easy for water vapor in the air to condense on the equipment's outer surface. Retained condensate increases the coating's water absorption, raises its wet thermal conductivity, and may cause corrosion of the metal substrate, blistering, cracking, or peeling of the coating. This invention, through the combination of coating composition and preparation process, enables the coating to simultaneously possess heat insulation, anti-condensation, superhydrophobic retention, and resistance to thermal cycling.

[0022] In the following embodiments, unless otherwise stated, all parts by weight are for each component, the water used is deionized water with a conductivity not exceeding 10 μS / cm, and the coating thickness refers to the dry film thickness; the silica aerogel used is Cabot's ENOVAIC 3100 hydrophobic silica aerogel powder, which is sieved before use to achieve a particle size of 5–80 μm, a pore size of 10–100 nm, and an apparent density of 0.08 g / cm³. 3 The waterborne siloxane-modified polyurethane-acrylic composite emulsion used was a custom-made WPUA-Si-45 emulsion with a solid content of 45±1%, a pH of 7.5–8.5, an average latex particle size of 80–150 nm, and a number-average molecular weight (Mn) of (6.0–8.0) × 10⁻⁶ for the tetrahydrofuran-soluble resin fraction after drying. 4 The phosphate-modified acrylic emulsion uses a custom PA-P-40 type emulsion with a solid content of 40±1%, an acid value of 15~25 mgKOH / g, and a number-average molecular weight Mn of (4.0~6.0)×10. 4 The silica sol used was SiSol-30 alkaline silica sol with a silica solid content of 30±1% and an average particle size of 10–20 nm; the hollow glass microspheres used were 3M S28HS type closed-cell borosilicate hollow glass microspheres with a true density of 0.28 g / cm³. 3 The average particle size is approximately 30 μm; the hydrophobic fumed silica used is Evonik's AEROSIL R972 product, with a specific surface area of ​​90–130 m². 2 / g; the flaky mica uses 800-mesh wet-process mica powder with an average particle size of 8–12 μm; γ-glycidoxypropyltrimethoxysilane uses KH-560 type, γ-aminopropyltriethoxysilane uses KH-550 type, and the purity of hexadecyltrimethoxysilane and tetraethyl silicate is not less than 98%; n-octadecane and n-eicosane use phase change grade products with a chemical purity of not less than 98%; the low-melting-point silicone wax is specifically C18 alkyl-modified polydimethylsiloxane wax with a number-average molecular weight Mn of (3.0–5.0) × 10 3The melting peak temperature was determined to be 30±2℃ by differential scanning calorimetry. The siloxane segment emulsifier used was a polyether-modified trisiloxane emulsifier with a number-average molecular weight (Mn) of 600–800. The isocyanate prepolymer was an aliphatic terminal isocyanate polyurethane prepolymer prepared from hexamethylene diisocyanate and polyether polyol, with a number-average molecular weight (Mn) of (2.0–2.5) × 10³ and an isocyanate group content of 5.5%–6.5%. The hydroxyl-containing polysiloxane used was α,ω-dihydroxypolydimethylsiloxane with a number-average molecular weight (Mn) of (1.8–2.2) × 10³. 3 The hydroxyl content is 1.5%–2.0% by mass; the polydimethylsiloxane is a single-terminated triethoxysilylpropyl-terminated polydimethylsiloxane with a number-average molecular weight Mn of (1.2–1.8) × 10⁻⁶. 3 The number-average molecular weight (Mn) of the hydroxyl-terminated polydimethylsiloxane used to prepare confined migration type low surface energy segment reservoirs is (4.5–5.5) × 10⁻⁶. 3 The purity of the nano-silica is not less than 99.5%, with an average particle size of 15–25 nm; the sheet thickness of the sheet-like nano-silicate is 1–5 nm, and the transverse dimension is 100–500 nm; the average particle size of the aluminum hydroxide is 3–8 μm; the expanded graphite is 80 mesh, and the expansion ratio is not less than 200 mL / g; the dispersant used is BYK-Chemie's DISPERBYK-190 aqueous dispersant; the defoamer used is BYK-024 aqueous organosilicon defoamer; the rheology modifier used is RHEOBYK-420 aqueous rheology modifier; and the film-forming aid used is Eastman's Texanol ester alcohol. Unless otherwise specified, the molecular weights of the above polymers are number average molecular weights determined by gel permeation chromatography, with tetrahydrofuran as the mobile phase and polystyrene as the calibration standard. The emulsion resin is determined from the dried soluble resin fraction.

[0023] This invention provides a method for preparing an anti-condensation and heat-insulating superhydrophobic aerogel coating, comprising the following steps: S1: Silica aerogel is modified in stages with reactive silane and hydrophobic silane in an alcohol-water mixed medium to obtain a bifunctional modified aerogel containing both resin-binding groups and low surface energy groups. S2: The phase change core material is emulsified into droplets, and an elastic intermediate layer, an inorganic nano-rough shell, and a bifacial outer surface with semi-through breathing channels are sequentially formed on the outside of the droplets to obtain dew point responsive bifacial breathing microcapsules. S3: Confined grafting of polysiloxanes with terminal hydroxyl, terminal epoxy, or terminal alkoxy groups to some bifunctional modified aerogels, silica sols, or dew-point responsive bifacial breathing microcapsules yields confined migration type low surface energy segment reservoirs. S4: A base slurry is obtained by mixing waterborne silicone-modified film-forming resin, sheet-like shielding filler, flame-retardant filler, dispersant, defoamer, rheology modifier, film-forming aid, and water. S5: Add the bifunctional modified aerogel, hollow heat-insulating microspheres and part of silica sol obtained in S1 to the base slurry obtained in S4, and mix them under low shear conditions to obtain aerogel heat-insulating slurry. S6: Add the dew-point responsive bifacial breathing microcapsules, hydrophobic nanoridge forming particles, and the confined migration type low surface energy chain segment reservoir obtained in S2 to the aerogel insulation slurry obtained in S5, adjust the pH value, wet film viscosity and solid content of the system, and obtain an anti-condensation heat-insulating superhydrophobic aerogel coating. S7: The anti-condensation and heat-insulating superhydrophobic aerogel coating obtained in S6 is applied to the outer surface of industrial thermal equipment, and leveling, pre-curing and post-curing are performed in sequence. This allows the dew point-responsive bifacial breathing microcapsules to accumulate on the side of the coating closest to the air, and together with the hydrophobic nanoridge particles and the confined migration low surface energy chain segment reservoir, they form a condensate droplet edge peeling structure, thus obtaining the anti-condensation and heat-insulating superhydrophobic aerogel coating.

[0024] like Figure 2 As shown in part (a), the bifunctional modified aerogel obtained in S1 retains its porous particle morphology. Its internal pore structure serves to block heat transfer. After surface modification with reactive and hydrophobic silanes, it can both form bonds with resins, silica sols, or other inorganic components and reduce the wetting ability of condensate on the aerogel pores. Figure 2 Part (b) and Figure 3 As shown, the dew-point responsive bifacial breathing microcapsule obtained by S2 includes a phase change core material 1, an elastic intermediate layer 2, an inorganic nano-roughened shell 3, a low surface energy side 4, a reactive bonding side 5, and a semi-through breathing channel 6. The phase change core material 1 buffers the surface temperature change of the coating near the dew point; the elastic intermediate layer 2 adapts to the volume change of the phase change core material 1; the inorganic nano-roughened shell 3 enhances the shell strength of the microcapsule and participates in constructing the roughened structure; the low surface energy side 4 forms a water-repellent surface towards the air interface; the reactive bonding side 5 bonds with the resin and inorganic components inside the coating; and the semi-through breathing channel 6 regulates the slow release of water vapor and restricts the entry of liquid water. Figure 2 As shown in section (c), hydrophobic nanoridge-forming particles are distributed around the microcapsules and on the coating surface to form nanoscale protrusions; as Figure 2 As shown in part (d), the cured coating forms an anchoring shield near the substrate, an aerogel insulation part in the middle, and a condensation repellency part near the air. The three parts work together to achieve heat preservation, anti-condensation, and superhydrophobic retention.

[0025] In the above preparation method, a thermally insulating framework with both low thermal conductivity and resin bonding strength is constructed through bifunctional modified aerogel; dew-point responsive breathing microcapsules simultaneously provide thermal buffering near the dew point, control of breathing channel opening and closing, surface elastic micro-protrusions, and low surface energy interfaces; the breathing microcapsules are oriented and enriched on the coating surface by charge, density, and film-forming viscosity windows; discrete nanoridges are constructed by hydrophobic nanoridge forming particles, causing edge depinning and peeling of condensed droplets during growth; and a confined migration type low surface energy chain segment reservoir provides limited hydrophobic reorientation capability after humid heat aging or slight wear. Therefore, this invention does not simply increase the initial water contact angle of the coating, but rather improves the stability of the superhydrophobic state in the condensation cycle, thermal cycle, and humid heat environment of industrial thermal equipment, reducing water absorption and the increase in wet thermal conductivity of the coating.

[0026] S1: Silica aerogel is modified in stages with reactive silane and hydrophobic silane in an alcohol-water mixed medium to obtain a bifunctional modified aerogel containing both resin-binding groups and low surface energy groups. In S1, the silica aerogel has a particle size of 5-80 μm, a pore size of 10-100 nm, and an apparent density of 0.04-0.20 g / cm³. 3 ; Reactive silanes include one or more of γ-glycidoxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane, methacryloyloxypropyltrimethoxysilane, or vinyltriethoxysilane; Hydrophobic silanes include one or more of octyltriethoxysilane, dodecyltrimethoxysilane, hexadecyltrimethoxysilane, methyltrimethoxysilane, or polydimethylsiloxane; The segmented modification involves first grafting reactive silanes at a pH of 4.0-6.0 and a temperature of 35-65℃ for 0.5-3 hours, and then grafting hydrophobic silanes at a pH of 7.0-9.5 and a temperature of 40-75℃ for 0.5-4 hours.

[0027] It should be noted that in S1, silica aerogel is the main porous filler that provides low thermal conductivity in the coating. Silica aerogel has nanoscale pores inside, and the gas in the pores has a barrier effect on heat transfer, thus reducing the thermal conductivity of the coating. When aerogel is added to water-based coatings as a powder, the compatibility and bonding strength between its particle surface and the water-based resin are insufficient, making it easy to form interfacial micro-defects during drying and thermal cycling. These micro-defects can become channels for water vapor and liquid water to enter the interior of the coating, and can also cause the thick coating to powder, crack, or partially peel off during thermal expansion and contraction. Therefore, this invention does not directly use ordinary aerogel powder, but first modifies silica aerogel in stages to make it have both resin bonding ability and low surface energy.

[0028] In S1, reactive silanes are used to introduce binding groups onto the surface of silica aerogel. γ-glycidoxypropyltrimethoxysilane provides epoxy groups, γ-aminopropyltriethoxysilane provides amino groups, methacryloyloxypropyltrimethoxysilane provides methacryloyloxy groups, and vinyltriethoxysilane provides vinyl groups. The alkoxy groups in these silanes can condense with the silanol groups on the aerogel surface after hydrolysis. The reactive organic groups can then bind with aqueous silicone-modified resins, silica sols, or other reactive components during the subsequent film formation process. As a result, the aerogel particles no longer exist only as fillers but can become part of the internal binding structure of the coating, which is beneficial for improving the coating's resistance to chalking and its integrity after thermal cycling.

[0029] Hydrophobic silanes in S1 are used to reduce the surface energy of the silica aerogel surface. Octyltriethoxysilane, dodecyltrimethoxysilane, and hexadecyltrimethoxysilane can form alkyl segments on the aerogel surface. Methyltrimethoxysilane can provide methylsiloxane structures, and polydimethylsiloxane can provide flexible siloxane segments. These low surface energy groups can reduce the wetting ability of condensate on aerogel particles and aerogel pores, reducing the possibility of liquid water entering the aerogel pores. If the aerogel is only hydrophobically modified without introducing reactive groups, the bonding between the aerogel and the resin is insufficient, and the coating is prone to interface defects under thick coating and thermal cycling conditions. If the aerogel is only reactively modified without introducing hydrophobic groups, although the aerogel particles can bond with the resin, they are easily wetted by water in condensation and humid environments, resulting in an increase in wet thermal conductivity. This invention combines both on the surface of the same aerogel particle, so that the aerogel simultaneously undertakes the functions of low thermal conductivity, low water absorption, and interface enhancement.

[0030] S1 employs a segmented approach, first grafting reactive silanes and then hydrophobic silanes. Reactive silane grafting is first performed at a pH of 4.0-6.0 and a temperature of 35-65℃, which helps control the hydrolysis and condensation rates of silanes, allowing epoxy, amino, methacryloyloxy, or vinyl groups to remain on the aerogel surface. Subsequently, hydrophobic silane grafting is performed at a pH of 7.0-9.5 and a temperature of 40-75℃, which facilitates the continued fixation of long-chain alkyl or siloxane structures on the aerogel surface, forming a low surface energy outer layer. If both types of silanes are added simultaneously, silane self-condensation and particle adhesion can easily occur, reducing the dispersibility of the aerogel powder. Segmented modification reduces these problems, making the aerogel easier to disperse in the base slurry in subsequent step S5, and providing binding sites for the confined grafting of polysiloxane segments in step S3.

[0031] S2: The phase change core material is emulsified into droplets, and an elastic intermediate layer, an inorganic nano-rough shell, and a bifacial outer surface with semi-through breathing channels are sequentially formed on the outside of the droplets to obtain dew point responsive bifacial breathing microcapsules. In S2, the phase change core material includes one or more of C14-C22 n-alkanes, fatty acid esters, low-melting-point silicone wax or paraffin, and the phase change temperature of the phase change core material is 15-42℃. The dew-point responsive bifacial respiratory microcapsules have a particle size of 5-50 μm, a shell thickness of 0.2-3.0 μm, and a semi-perforated breathing channel pore size of 5-80 nm. The elastic interlayer includes one or more of polyurea, polyurethane, polysiloxane, or acrylate elastomer; Inorganic nano-rough shells include one or more of silica, silica sol condensate, silsesquioxane, nano-alumina, or sheet silicates. The bifacial outer surface includes a low surface energy side and a reactive bonding side. The low surface energy side contains one or more of polydimethylsiloxane segments, C8-C18 alkylsiloxane segments, or phenylsiloxane segments, while the reactive bonding side contains one or more of hydroxyl, amino, epoxy, carboxyl, or alkenyl groups.

[0032] It should be noted that, as Figure 3 As shown, the dew-point responsive bifacial breathing microcapsule is not a single-shell microcapsule, but rather comprises, from the inside out, a phase change core material 1, an elastic intermediate layer 2, an inorganic nano-roughened shell 3, and a bifacial outer surface with a low surface energy side 4, a reactive bonding side 5, and semi-through breathing channels 6. This structure allows the phase change core material 1 of the microcapsule in the coating system to undergo an endothermic and exothermic process when the surface temperature of the equipment approaches the dew point, thereby slowing down the rapid drop of the coating surface temperature below the dew point. Furthermore, the semi-through breathing channels 6 allow for limited release of water vapor without forming a through channel for liquid water to directly enter the microcapsule. Additionally, the low surface energy side 4 tends to face the air interface during coating curing, while the reactive bonding side 5 bonds with resin, silica sol, or aerogel, thus preventing the microcapsule from existing solely as a free filler. Figure 3 The structure shown corresponds to the preparation steps of the phase change core material, elastic intermediate layer, inorganic nano-rough shell layer and bifacial outer surface in S2.

[0033] The dew-point responsive bifacial breathing microcapsules prepared by S2 are used to solve the problem of ordinary superhydrophobic coatings easily failing under condensation conditions. Ordinary superhydrophobic coatings usually improve the water contact angle through low surface energy materials and micro / nano rough structures. However, during the condensation process, water vapor in the air may directly nucleate inside the micro / nano structure instead of first forming macro water droplets and then contacting the coating surface. After the water vapor nucleates and grows inside the rough structure, it will fill the tiny gaps that should have retained air, increasing the contact area between the water droplets and the solid surface, and thus forming highly adhered droplets or continuous water films. This process causes the aerogel channels to absorb moisture, resulting in an increase in the wet thermal conductivity of the coating. This invention uses dew-point responsive bifacial breathing microcapsules to form a structure with heat buffering, liquid water entry inhibition, and droplet desorption capabilities on the side of the coating closest to the air.

[0034] The phase change core material is selected from C14-C22 n-alkanes, fatty acid esters, low-melting-point silicone wax, or paraffin wax because these materials can adjust the phase change temperature by adjusting the carbon chain length and composition ratio, keeping it within the range of 15-42℃. This temperature range is suitable for the temperature range where condensation may occur on the outer surface of various industrial thermal equipment in high-humidity environments. When the temperature of the outer surface of the equipment approaches the dew point, the phase change core material undergoes an endothermic or exothermic process, which can slow down the temperature change on the side of the coating closest to the air and reduce the degree to which the local surface rapidly falls below the dew point, thereby delaying the formation of condensation droplets and the generation of a continuous water film. The phase change core material is encapsulated inside microcapsules, avoiding the problems of exudation, resin softening, and contamination of the superhydrophobic surface that may occur when the phase change material is directly dispersed in the coating.

[0035] An elastic intermediate layer is placed on the outside of the phase change core material to withstand the volume change of the phase change core material during the solid-liquid transition process. Polyurea, polyurethane, polysiloxane, or acrylate elastomers can all provide a certain degree of flexibility, making the microcapsules less prone to shell cracking during thermal cycling. An inorganic nano-rough shell layer is placed on the outside of the elastic intermediate layer to improve the shell strength of the microcapsules and provide inorganic components for the micro-nano structure of the coating surface. Silica, silica sol condensate, silsesquioxane, nano-alumina, and lamellar silicates can all combine or intercalate with silica sol, waterborne silicone-modified resin, and aerogel in the coating, making the microcapsules less prone to loosening in the coating.

[0036] The pore size of the semi-through breathing channel is limited to 5-80 nm. This channel is not a straight through hole that runs directly from the outer surface of the microcapsule to the interior of the phase change core material. Instead, it forms a tortuous or incompletely penetrating fine channel in the shell. This structure allows a small amount of water vapor inside the coating to be released slowly at higher temperatures. At the same time, when the temperature is close to the dew point and liquid water appears, the hydrophobicity of the pore wall and the limitation of the pore size reduce the entry of liquid water. If the pore size is too small, the release of water vapor will be hindered. If the pore size is too large, the risk of liquid water entering and contaminating the interior of the microcapsule will increase. The limitation of 5-80 nm allows the microcapsule to participate in moisture regulation without becoming a direct passage for liquid water to enter the interior of the coating.

[0037] The bifacial outer surface consists of a low surface energy side and a reactive bonding side. The low surface energy side contains polydimethylsiloxane segments, C8-C18 alkylsiloxane segments, or phenylsiloxane segments, which are more likely to be located on the air-facing side of the coating during subsequent film formation, thereby improving the coating surface's ability to repel water droplets. The reactive bonding side contains hydroxyl, amino, epoxy, carboxyl, or alkenyl groups, which can bind with resins, silica sols, bifunctional modified aerogels, or other inorganic particles. If all the outer surfaces of the microcapsules are low surface energy structures, they will be difficult to disperse in water-based coatings and will not be conducive to bonding with the interior of the coating. If all the outer surfaces of the microcapsules are hydrophilic or reactive structures, they will easily become nucleation sites for condensation. The bifacial outer surface enables the microcapsules to simultaneously possess the anti-condensation effect on the air-facing side and the bonding ability on the coating interior side.

[0038] S3: Confined grafting of polysiloxanes with terminal hydroxyl, terminal epoxy, or terminal alkoxy groups to some bifunctional modified aerogels, silica sols, or dew-point responsive bifacial breathing microcapsules yields confined migration type low surface energy segment reservoirs. In S3, in the confined migration type low surface energy segment reservoir, one end of the polysiloxane segment forms a silicon-oxygen bond, hydrogen bond or covalent bond with the shell of bifunctional modified aerogel, silica sol or dew point responsive bifacial breathing microcapsule, while the other end is a low surface energy segment that can be reoriented to the coating surface after heat treatment at 40-100℃. In confined migration type low surface energy chain segment storage, the mass of free polysiloxane accounts for 0-15% of the total polysiloxane mass.

[0039] It should be noted that S3 is used to improve the superhydrophobicity retention of the coating after humid heat aging, slight wear, and thermal cycling. The outer surface of industrial thermal equipment is affected by dust, oil mist, friction, and temperature changes during installation, operation, and maintenance. The low surface energy segments on the coating surface may be covered by contaminants or reduced due to friction, which reduces the water contact angle and increases the roll-off angle. If only the initial hydrophobic particles and hydrophobic agents are relied upon, the coating is prone to losing its superhydrophobic state after a period of use. In step S3 of this invention, a confined migration type low surface energy segment reservoir is prepared, so that the low surface energy segments can be reoriented to the coating surface during subsequent heat treatment or equipment operation and heating, thereby replenishing the low surface energy of the surface.

[0040] Hydroxyl-terminated, epoxy-terminated, or alkoxy-terminated polysiloxanes possess both low surface energy siloxane segments and end groups capable of binding with inorganic or organic components. Hydroxyl-terminated polydimethylsiloxanes can condense with silanol groups on the surface of aerogels or silica sols. Alkoxy-terminated polysiloxanes can form silanol groups after hydrolysis and undergo further condensation. Epoxy-terminated polysiloxanes can react with amino or hydroxyl groups. Through these reactions, one end of the polysiloxane segment is fixed near the shell of a bifunctional modified aerogel, silica sol, or dew-point responsive bifacial respiratory microcapsule, while the other end retains the orientation capability of the low surface energy siloxane segment.

[0041] The confined migration type low surface energy segment reservoir differs from the direct addition of free silicone oil. Free silicone oil tends to migrate disorderly, potentially precipitating in large quantities on the coating surface or migrating towards the substrate, causing surface stickiness, dust absorption, difficulty in recoating, and decreased adhesion. This invention confines one end of the polysiloxane segment to the vicinity of an aerogel, silica sol, or microcapsule shell, allowing it to orient within a certain range and preventing it from flowing in large quantities like free silicone oil. The proportion of free polysiloxane in the reservoir to the total polysiloxane mass is limited to 0-15% to control the content of unbound polysiloxane. When the free polysiloxane content is too high, the coating is prone to surface stickiness and decreased adhesion after long-term use; when the free polysiloxane content is too low and the binding is too strong, the hydrophobic recovery ability of the coating after wear is insufficient. This proportion limit allows the coating to achieve an appropriate balance between hydrophobic recovery and interface stability.

[0042] This allows the bifunctional modified aerogel obtained through S1 to provide grafting sites for polysiloxane segments, and the inorganic nano-rough shell and bifacial outer surface obtained through S2 to also provide bonding sites for polysiloxane segments. Finally, the confined migration type low surface energy segment reservoir obtained through S3 is added to the coating in S6, and surface orientation occurs during the post-curing and subsequent use heating process in S7, so that the coating can still maintain a high contact angle and a low roll-off angle after condensation cycles.

[0043] S4: A base slurry is obtained by mixing waterborne silicone-modified film-forming resin, sheet-like shielding filler, flame-retardant filler, dispersant, defoamer, rheology modifier, film-forming aid, and water. In S4, the waterborne silicone-modified film-forming resin includes one or more of the following: waterborne silicone-modified polyurethane emulsion, waterborne silicone-acrylic emulsion, waterborne siloxane-modified polyurethane-acrylic composite emulsion, or phosphate ester-modified acrylic emulsion. The sheet-like shielding filler includes one or more of mica, sericite, sheet-like silicate, hexagonal boron nitride, sheet-like alumina, or sheet-like ceramic filler; Flame-retardant fillers include one or more of aluminum hydroxide, magnesium hydroxide, expanded graphite, ammonium polyphosphate, melamine polyphosphate, or zinc borate; It should be noted that S4 is used to form a base slurry capable of supporting subsequent thermal insulation fillers and anti-condensation functional particles. The waterborne silicone-modified film-forming resin is the continuous phase of the coating, enabling the powder and functional particles to solidify and form a complete coating, which then adheres to the outer surface of the metal equipment. The waterborne silicone-modified polyurethane emulsion has flexibility and can buffer the thermal stress caused by thermal cycling. The waterborne silicone-acrylic emulsion has good water resistance and film-forming properties. The waterborne siloxane-modified polyurethane-acrylic composite emulsion can balance flexibility, water resistance, and compatibility with low surface energy components. The phosphate groups in the phosphate ester-modified acrylic emulsion can improve the adhesion of the coating to the surface of steel, aluminum alloy, stainless steel, or galvanized parts. Therefore, the above resins can be used alone or in combination according to different equipment outer surface materials and operating temperatures.

[0044] Flaky shielding fillers are used to extend the migration path of water vapor, oxygen and corrosive media to the substrate side. Mica, sericite, flaky silicate, hexagonal boron nitride, flaky alumina or flaky ceramic fillers all have flaky morphology and are easy to form a near-parallel arrangement during the coating drying process, thereby improving the shielding and crack resistance of the coating. Flaky fillers can also work with resin and silica sol to improve the dimensional stability of thick coatings and reduce the brittleness caused by high content of aerogel and hollow microspheres.

[0045] Flame-retardant fillers are used to improve the safety of coatings on the outer surfaces of industrial thermal equipment. Aluminum hydroxide and magnesium hydroxide release bound water and absorb heat when heated. Expanded graphite forms an expanded carbon layer after heating. Ammonium polyphosphate, melamine polyphosphate, or zinc borate can participate in the flame-retardant and smoke-suppressing process. Dispersants are used to reduce powder agglomeration, so that the flake fillers, flame-retardant fillers, and subsequently added aerogel can be uniformly dispersed. Defoamers are used to reduce bubbles generated during mixing and construction, and to avoid the formation of pore defects after the coating is cured. Rheology modifiers are used to control the anti-sagging and leveling ability of the slurry during thick coating construction. Film-forming aids are used to promote the fusion and film formation of water-based resins during drying. Thus, the stability of the base slurry obtained through S4 directly affects the dispersion state of aerogel and hollow microspheres in S5, and also affects the distribution of microcapsules and nanoparticles in S6.

[0046] S5: Add the bifunctional modified aerogel, hollow heat-insulating microspheres and part of silica sol obtained in S1 to the base slurry obtained in S4, and mix them under low shear conditions to obtain aerogel heat-insulating slurry. In S5, hollow thermal insulation microspheres include one or more of hollow glass microspheres, hollow ceramic microspheres, closed-cell expanded microspheres, or hollow silicate microspheres, with a particle size of 10-120 μm and an apparent density of 0.10-0.60 g / cm³. 3 The low shear conditions are a rotation speed of 100-800 r / min and a mixing time of 5-40 min.

[0047] It should be noted that S5 is used to form an aerogel insulation slurry that provides thermal insulation. The bifunctional modified aerogel contains a nanoporous structure, which can reduce gas conduction and solid skeleton conduction. The hollow insulation microspheres contain a closed-cell structure, which can provide micron-level insulation units in the coating. The bifunctional modified aerogel and hollow insulation microspheres are used together to reduce the excessive viscosity of the slurry and the decrease in coating strength caused by using a large amount of aerogel alone. It can also avoid the problem of insufficient reduction in thermal conductivity when using hollow microspheres alone. Some silica sol is added to S5, which can form inorganic bonding points during drying and curing, and improve the bonding force between aerogel, hollow microspheres, sheet filler and resin.

[0048] The particle size of hollow thermal insulation microspheres is limited to 10-120 μm. If the particle size is too small, the contribution of the closed-cell structure to the thermal insulation performance decreases, and the viscosity of the slurry increases. If the particle size is too large, the surface smoothness of the coating decreases, and local defects are more likely to occur. The apparent density is limited to 0.10-0.60 g / cm³. 3 This is to ensure that hollow heat-insulating microspheres have good dispersion stability and heat insulation effect in coatings. Hollow glass microspheres have good dimensional stability and low thermal conductivity, while hollow ceramic microspheres have good temperature resistance. Closed-cell expanded microspheres and hollow silicate microspheres can be selected according to the coating's operating temperature and cost requirements.

[0049] Low-shear mixing is necessary because both aerogel and hollow microspheres have porous or hollow structures. Excessive shear can damage hollow microspheres and may also cause excessive resin penetration into the aerogel pores, reducing the insulation effect. Controlling the rotation speed to 100-800 r / min and the mixing time to 5-40 min allows the bifunctional modified aerogel and hollow insulating microspheres to be dispersed in the base slurry while reducing structural damage. This enables the bifunctional modified aerogel to better combine with the resin and silica sol, reducing aerogel powder agglomeration. At the same time, the aerogel insulating slurry provides an applyable carrier system for dew-point responsive bifacial breathing microcapsules and hydrophobic nanoridge forming particles, allowing the middle of the coating to bear the insulation effect and the side of the coating closest to the air to bear the anti-condensation effect.

[0050] S6: Add the dew-point responsive bifacial breathing microcapsules, hydrophobic nanoridge forming particles, and the confined migration type low surface energy chain segment reservoir obtained in S2 to the aerogel insulation slurry obtained in S5, adjust the pH value, wet film viscosity and solid content of the system, and obtain an anti-condensation heat-insulating superhydrophobic aerogel coating. In step S6, the hydrophobic nanoridge forming particles include one or more of the following: chain-like nano silica, fumed silica, hydrophobically modified silica sol, sheet-like nano silicates, nano alumina, or nano sericite, with a particle size or thickness of 10-500 nm; in step S6, the pH value of the system is adjusted to 7.5-9.5, the wet film viscosity is adjusted to 3000-12000 mPa·s, and the solid content is adjusted to 45-78%.

[0051] It should be noted that S6 is used to introduce anti-condensation and superhydrophobic functional components into the aerogel insulation slurry, and to make the coating suitable for thick coating application and subsequent film formation. After the dew point responsive bifacial breathing microcapsules are added in step S6, they can accumulate on the side of the coating closer to the air during subsequent leveling and curing, forming a micron-scale elastic micro-protrusion structure, and providing heat buffering and breathing channel regulation near the dew point. Hydrophobic nanoridge forming particles form nanoscale protrusions around the microcapsules and on the coating surface, reducing the actual contact area between condensate droplets and the coating, and promoting the desorption of droplet edges first. The confined migration type low surface energy chain segment reservoir enters the coating system in step S6, and replenishes the low surface energy chain segments on the coating surface during subsequent curing and use.

[0052] The hydrophobic nanoridge forming particles are selected from chain-like nano-silica, fumed silica, hydrophobically modified silica sol, sheet-like nano-silicate, nano-alumina, or nano-sericite. These particles can form nanoscale protrusions on the surface and between the micron-scale microcapsules. Chain-like nano-silica and fumed silica can form discontinuous nano-protrusions. Hydrophobically modified silica sol can form a bond with silica sol and resin during curing. Sheet-like nano-silicate, nano-alumina, and nano-sericite can form sheet-like edge structures. The particle size or thickness is limited to 10-500 nm to enable the formation of nanoscale rough structures while avoiding the formation of excessively thick continuous layers. If the particles are too small and the dosage is too high, it is easy to increase the viscosity of the slurry and cause agglomeration. If the particles are too large, it is difficult to cooperate with the microcapsules to form a condensation droplet edge peeling structure.

[0053] In step S6, the pH value is adjusted to 7.5-9.5, which is conducive to the continued condensation between silica sol, silane residual groups, and inorganic shells, while maintaining the stability of the waterborne resin system. The wet film viscosity is adjusted to 3000-12000 mPa·s to ensure that the coating has sufficient fluidity after application to allow for limited migration of microcapsules, while also having sufficient anti-sagging ability to prevent excessive floating or settling of microcapsules. The solid content is adjusted to 45-78%, which is conducive to thick coating application and reduces drying shrinkage. The distribution state of each component in the coating obtained in step S6 is transformed into the specific structure of the coating during leveling and curing in step S7. Therefore, this step has a direct impact on the final anti-condensation performance.

[0054] S7: The anti-condensation and heat-insulating superhydrophobic aerogel coating obtained in S6 is applied to the outer surface of industrial thermal equipment, and leveling, pre-curing and post-curing are performed in sequence. This allows the dew point-responsive bifacial breathing microcapsules to accumulate on the side of the coating closest to the air, and together with the hydrophobic nanoridge particles and the confined migration low surface energy chain segment reservoir, they form a condensate droplet edge peeling structure, thus obtaining the anti-condensation and heat-insulating superhydrophobic aerogel coating.

[0055] In S7, the leveling temperature is 15-35℃ and the time is 5-30 min; the pre-curing temperature is 40-80℃ and the time is 0.5-3 h; the post-curing temperature is 60-110℃ and the time is 1-8 h; the dry film thickness of the resulting anti-condensation and heat-insulating superhydrophobic aerogel coating is 0.5-5.0 mm; the height of the dew point responsive bifacial breathable microcapsules protruding from the coating surface is 10-45% of their particle size, and the spacing between adjacent dew point responsive bifacial breathable microcapsules is 5-80 μm.

[0056] It should be noted that, as Figure 2As shown in section (d), the coating obtained by S7 curing is not a uniform, randomly dispersed filler structure, but rather a composite structure with functional zones along the thickness direction. On the side near the substrate, it consists of water-based silicone-modified film-forming resin, sheet-like shielding filler, flame-retardant filler, and some silica sol, used to improve the adhesion between the coating and the outer surface of industrial thermal equipment and to extend the migration path of water vapor towards the substrate. The middle part of the coating mainly consists of bifunctional modified aerogel and hollow heat-insulating microspheres, used to form a low thermal conductivity insulation region. On the side near the air, it consists of dew-point responsive bifacial breathing microcapsules, hydrophobic nanoridge-forming particles, and confined migration-type low surface energy chain segment reservoirs, used to form a condensation-repelling section. Figure 2 The exposed state of the microcapsule portion in part (d) corresponds to the height of the dew point-responsive bifacial breathing microcapsule in S7 protruding from the coating surface by 10-45% of its particle size. This exposed state enables the condensed droplets to be supported by micron-scale micro-protrusions, and under the synergistic effect of the nano-ridge structure, edge destabilization and peeling preferentially occur.

[0057] S7 is used to transform coatings into cured coatings with anti-condensation, heat preservation, and adhesion capabilities. After the coating is applied to the outer surface of industrial thermal equipment, the leveling stage is carried out at 15-35℃ for 5-30 minutes. This allows the dew point-responsive bifacial breathing microcapsules in the wet film to accumulate to a limited extent on the side closer to the air under the combined effects of buoyancy, surface energy difference, and slurry flow. This accumulation does not cause the microcapsules to float completely out of the coating, but rather to partially remain on or near the surface of the coating. The reaction bonding side remains in contact with the resin, aerogel, and silica sol. If the leveling time is too short, the microcapsules will not accumulate sufficiently on the side closer to the air; if the leveling time is too long, the microcapsules are prone to local aggregation, affecting the uniformity of the coating.

[0058] The pre-curing stage is carried out at 40-80℃ for 0.5-3 hours, allowing moisture and some film-forming aids to evaporate, and enabling the resin particles to fuse, silica sol to condense, and silane residual groups to react gradually. The role of pre-curing is to fix the distribution of microcapsules on the air-facing side of the coating and prevent them from migrating further. The post-curing stage is carried out at 60-110℃ for 1-8 hours, further improving the bonding between the resin, silica sol, silane-modified aerogel, and inorganic particles, while also orienting restricted migration low surface energy segments toward the coating surface, thereby improving the low surface energy of the coating after curing and its hydrophobic retention ability after condensation cycles.

[0059] The height of the dew-point responsive bifacial breathing microcapsules protruding from the coating surface is limited to 10-45% of their particle size. If the protrusion height is too low, the microcapsules are difficult to form an effective elastic micro-convex structure, and condensate droplets are easily trapped in the rough structure. If the protrusion height is too high, the coating's abrasion resistance decreases, and the microcapsules are easily detached due to friction. The spacing between adjacent microcapsules is limited to 5-80 μm. If the spacing is too small, the surface is excessively rough and dust is easily trapped. If the spacing is too large, there is insufficient support under the droplets, and condensate droplets are difficult to discharge through edge desorption. Through this structure, during the growth process, condensate droplets first undergo local desorption at the edge of the three-phase contact line, and then undergo overall sliding or rolling, thereby reducing the formation of a continuous water film.

[0060] The above-mentioned materials, by weight, comprise 18-45 parts of waterborne silicone-modified film-forming resin, 8-32 parts of bifunctional modified aerogel, 4-20 parts of hollow heat-insulating microspheres, 4-18 parts of dew-point responsive bifacial breathing microcapsules, 1-8 parts of hydrophobic nanoridge-forming particles, 2-14 parts of silica sol, 1-10 parts of sheet-like shielding filler, 5-25 parts of flame-retardant filler, 0.5-6 parts of confined migration type low surface energy chain segment reservoir, 0.2-2 parts of dispersant, 0.1-1 part of defoamer, 0.2-3 parts of rheology modifier, 0.5-5 parts of film-forming aid, and 20-70 parts of water.

[0061] It should be noted that the above proportions are used to ensure that the coating has workability, thermal insulation, anti-condensation, adhesion, and durability. When the water-based silicone-modified film-forming resin is less than 18 parts, the coating continuity and adhesion are insufficient; when it is more than 45 parts, the relative content of thermal insulation filler decreases and the thermal conductivity increases; when the bifunctional modified aerogel is less than 8 parts, its contribution to thermal insulation is insufficient; when it is more than 32 parts, the slurry viscosity increases and the coating brittleness increases; when the hollow thermal insulation microspheres are less than 4 parts, the closed-cell thermal insulation effect is insufficient; when it is more than 20 parts, the coating strength decreases; when the dew point-responsive bifacial breathing microcapsules are less than 4 parts, the surface anti-condensation effect is insufficient; when it is more than 18 parts, the microcapsule spacing is too small, the coating wear resistance and surface uniformity decrease; when the hydrophobic nanoridge forming particles are less than 1 part, it is difficult to form effective nano-protrusions; when it is more than 8 parts, the tendency of particle agglomeration increases; when the restricted migration type low surface energy chain segment reservoir is less than 0.5 parts, the hydrophobic recovery effect is insufficient; when it is more than 6 parts, it may affect the coating adhesion and surface cleanliness.

[0062] The present invention also provides an anti-condensation and heat-insulating superhydrophobic aerogel coating. The coating formed after curing includes an anchoring shielding part near the substrate, an aerogel heat insulation part in the middle, and a condensation repellent part near the air. The water contact angle of the coating is 150-168°, the roll-off angle is 1-10°, the dry thermal conductivity is 0.028-0.060W / (m·K), the water contact angle retention rate is 85-98% after 50 condensation cycles, and there is no cracking, blistering or peeling after 100 cold and hot cycles.

[0063] It should be noted that the coating structure of the aforementioned anti-condensation and heat-insulating superhydrophobic aerogel coating is the result of the combined action of S1 to S7. The anchoring and shielding part near the substrate is mainly composed of water-based silicone-modified film-forming resin, phosphate-modified resin, and sheet-like shielding filler. Its function is to improve the adhesion of the coating to the metal substrate and delay the migration of water vapor and corrosive media to the substrate side. The aerogel heat insulation part in the middle is mainly composed of bifunctional modified aerogel, hollow heat insulation microspheres, silica sol, and resin. Its function is to reduce heat transfer. The condensation repellency part near the air is mainly composed of dew-point responsive bifacial breathing microcapsules, hydrophobic nanoridge forming particles, and confined migration type low surface energy chain segment reservoirs. Its function is to delay the formation of continuous water film and promote the desorption of condensate droplets. The water contact angle, roll-off angle, dry thermal conductivity, contact angle retention rate after condensation cycle, and appearance integrity after thermal cycling are used to illustrate that the coating can simultaneously meet the anti-condensation and heat insulation requirements on the outer surface of industrial thermal equipment.

[0064] This invention also provides an application of an anti-condensation and heat-insulating superhydrophobic aerogel coating in the anti-condensation and heat-insulating treatment of the outer surface of industrial thermal equipment, including cryogenic storage tanks, chilled water pipelines, heat exchanger shells, outer walls of reactor jackets, cooling sections of steam pipelines during shutdown, cooling pipelines after compressed air, heat pump equipment shells, cooling unit shells, or the outer surface of metal equipment that periodically crosses dew point conditions.

[0065] It should be noted that the application of this invention is for the outer surfaces of industrial thermal equipment that are at risk of condensation. Low-temperature storage tanks, chilled water pipelines, compressed air aftercooling pipelines, heat pump equipment shells, and cooling unit shells are prone to condensation in high-humidity environments. Heat exchanger shells, reactor jacket outer walls, and steam pipeline shutdown cooling sections experience temperature changes during start-up and shutdown, and the outer surface temperature may periodically approach or fall below the ambient dew point. The outer surfaces of the aforementioned equipment need to reduce heat transfer and minimize condensation retention. When the coating of this invention is used on such surfaces, it can reduce heat flux density through the aerogel insulation portion, reduce continuous water film formation through the condensation repellency portion, and improve adhesion and protection to the metal substrate through the anchoring shielding portion.

[0066] Example 1: This example prepares an anti-condensation and heat-insulating superhydrophobic aerogel coating suitable for the outer surface of chilled water pipelines.

[0067] 100 parts of silica aerogel were added to a mixture of 1200 parts of ethanol and water at a mass ratio of 4:1. The pH was adjusted to 5.0, and 8 parts of γ-glycidoxypropyltrimethoxysilane were added. The mixture was reacted at 50°C for 2 hours. Subsequently, the pH was adjusted to 8.5, and 12 parts of hexadecyltrimethoxysilane were added. The mixture was reacted at 60°C for 2 hours. After solid-liquid separation, washing with ethanol, and drying at 60°C, a bifunctional modified aerogel was obtained.

[0068] 80 parts of n-octadecane and 20 parts of low-melting-point silicone wax with a melting point of 30℃ were mixed and heated to 45℃ to melt. 3 parts of a siloxane-containing segment emulsifier and 4 parts of nano-silica were added, and the mixture was emulsified in an aqueous phase to form emulsion droplets with an average particle size of approximately 20 μm. 18 parts of isocyanate prepolymer and 8 parts of hydroxyl-containing polysiloxane were added to the emulsion, and the mixture was reacted at 45℃ for 1.5 h to form an elastic intermediate layer. Subsequently, 20 parts of tetraethyl silicate and 4 parts of γ-aminopropyl + ethoxysilane were added, and the mixture was reacted at pH 8.0 and 45℃ for 2 h to form an inorganic nano-rough shell. Five parts of polydimethylsiloxane and three parts of sheet-like nanosilicate were added, and the reaction was continued at 45°C for 1 hour. After the reaction, the system was cooled to 25°C and centrifuged to obtain wet microcapsule material. The obtained wet microcapsule material was added to a 0.01 mol / L sodium hydroxide aqueous solution at a liquid-to-solid ratio of 1 g:20 mL, and alkali washed at 25°C and 200 r / min for 15 min to selectively remove the insufficiently condensed silica components in the inorganic nano-rough shell and form initial nanopores. After alkali washing, the microcapsules were centrifuged and washed with deionized water until the pH of the supernatant was 7.0. The washed microcapsules were then... The polydimethylsiloxane segments in the shell were added to a mixed solution of ethanol and water in a volume ratio of 7:3 and gently swollen for 20 min at 30 °C and 100 r / min, allowing limited expansion of the polydimethylsiloxane segments in the shell. After swelling, the mixture was centrifuged and washed twice with a 30% ethanol aqueous solution and once with deionized water. The mixture was then vacuum dried at 40 °C for 12 h, causing the swollen segments to shrink and form tortuous breathing channels in the inorganic shell that do not completely penetrate the shell. This yielded dew-point responsive bifacial breathing microcapsules with an average particle size of approximately 22 μm, a shell thickness of approximately 1.2 μm, and an average pore size of approximately 30 nm for the semi-penetrating breathing channels.

[0069] 10 parts of hydroxyl-terminated polydimethylsiloxane, 30 parts of bifunctional modified aerogel and 20 parts of silica sol were mixed, the pH was adjusted to 8.5, and the mixture was reacted at 55°C for 2 hours. After drying, the mixture was lightly pulverized to obtain a confined migration type low surface energy segment reservoir.

[0070] A base slurry was prepared by mixing 30 parts of waterborne siloxane-modified polyurethane-acrylic composite emulsion, 8 parts of phosphate ester-modified acrylic emulsion, 30 parts of water, 0.8 parts of dispersant, 0.4 parts of defoamer, 1.2 parts of rheology modifier, 2 parts of film-forming aid, 4 parts of flake mica, 10 parts of aluminum hydroxide, and 3 parts of expanded graphite. 20 parts of bifunctional modified aerogel, 10 parts of hollow glass microspheres, and 6 parts of silica sol were added to the base slurry, and the mixture was stirred at 400 r / min for 20 min to obtain an aerogel insulation slurry. 10 parts of dew-point responsive bifacial breathing microcapsules, 3 parts of hydrophobic fumed silica, and 3 parts of confined migration-type low surface energy segment reservoirs were added to the aerogel insulation slurry, and the pH was adjusted to 8.5. The wet film viscosity was 6800 mPa·s, and the solid content was 62%, resulting in an anti-condensation and heat-insulating superhydrophobic aerogel coating.

[0071] The obtained coating was applied to the surface of a carbon steel plate that had been degreased, derusted, and primed. The coating was applied in three coats, with a final dry film thickness of 2.0 mm. The coating was leveled at 25°C for 15 min, pre-cured at 60°C for 1.5 h, and post-cured at 85°C for 3 h to obtain an anti-condensation and heat-insulating superhydrophobic aerogel coating.

[0072] Example 2: This example is based on Example 1, but the particle size of the silica aerogel in step S1 is adjusted to 5 μm, while other parameters remain unchanged.

[0073] Example 3: This example is based on Example 1, except that the particle size of the silica aerogel in step S1 is adjusted to 80 μm, while other parameters remain unchanged.

[0074] Example 4: Based on Example 1, this example adjusts the grafting temperature of the reactive silane in step S1 to 35°C and the reaction time to 3 hours, while keeping other parameters unchanged.

[0075] Example 5: Based on Example 1, this example adjusts the grafting temperature of the reactive silane in step S1 to 65°C and the reaction time to 0.5 h, while keeping other parameters unchanged.

[0076] Example 6: This example is based on Example 1, except that the grafting temperature of the hydrophobic silane in step S1 is adjusted to 40°C and the reaction time is adjusted to 4 hours, while other parameters remain unchanged.

[0077] Example 7: This example is based on Example 1, except that the grafting temperature of the hydrophobic silane in step S1 is adjusted to 75°C and the reaction time is adjusted to 0.5 h, while other parameters remain unchanged.

[0078] Example 8: Based on Example 1, this example adjusts the emulsification shearing speed in S2 to 8000 r / min and the shearing time to 12 min, while keeping other parameters unchanged, thereby obtaining dew point responsive bifacial respiratory microcapsules with an average particle size of about 5 μm.

[0079] Example 9: Based on Example 1, this example adjusts the emulsification shearing speed in S2 to 1200 r / min and the shearing time to 5 min, while keeping other parameters unchanged, thereby obtaining dew point responsive bifacial respiratory microcapsules with an average particle size of about 50 μm.

[0080] Example 10: Based on Example 1, this example adjusts the concentration of sodium hydroxide aqueous solution used for alkaline washing in S2 to 0.003 mol / L, the alkaline washing time to 5 min, the volume ratio of ethanol / water mixed solution to 3:7, and the swelling time to 10 min, while keeping other parameters unchanged, thereby obtaining dew point responsive bifacial respiratory microcapsules with an average pore size of approximately 5 nm for semi-through breathing channels.

[0081] Example 11: Based on Example 1, this example adjusts the concentration of sodium hydroxide aqueous solution used for alkaline washing in S2 to 0.02 mol / L, the alkaline washing time to 25 min, the volume ratio of ethanol / water mixed solution to 8:2, and the swelling time to 25 min, while keeping other parameters unchanged, thereby obtaining dew point responsive bifacial respiratory microcapsules with an average pore size of approximately 80 nm for semi-through breathing channels.

[0082] Example 12: Based on Example 1, this example adjusts the phase change core material in S2 to 60 parts of n-hexadecane, 30 parts of n-tetradecane and 10 parts of low melting point silicone wax, while keeping other parameters unchanged, thereby obtaining a dew point responsive bifacial breathing microcapsule with a phase change temperature of about 15°C.

[0083] Example 13: Based on Example 1, this example adjusts the phase change core material in S2 to 50 parts n-eicosane, 40 parts n-docosahexanes and 10 parts low-melting-point silicone wax, while keeping other parameters unchanged, thereby obtaining a dew-point responsive bifacial breathing microcapsule with a phase change temperature of about 42°C.

[0084] Example 14: Based on Example 1, this example adjusts the pH value of the system in S6 to 7.5 while keeping other parameters unchanged, thereby obtaining an anti-condensation and heat-insulating superhydrophobic aerogel coating with a pH value of 7.5.

[0085] Example 15: Based on Example 1, this example adjusts the pH value of the system in S6 to 9.5 while keeping other parameters unchanged, thereby obtaining an anti-condensation and heat-insulating superhydrophobic aerogel coating with a pH value of 9.5.

[0086] Example 16: Based on Example 1, this example adjusts the amount of rheology modifier added in S6 to 0.25 parts, while keeping other parameters unchanged, thereby obtaining an anti-condensation and heat-insulating superhydrophobic aerogel coating with a wet film viscosity of 3000 mPa·s.

[0087] Example 17: Based on Example 1, this example adjusts the amount of rheology modifier added in S6 to 2.8 parts, while keeping other parameters unchanged, thereby obtaining an anti-condensation and heat-insulating superhydrophobic aerogel coating with a wet film viscosity of 12000 mPa·s.

[0088] Example 18: Based on Example 1, this example adjusts the amount of deionized water added in S6 to adjust the solid content of the system to 45%, while keeping other parameters unchanged, thereby obtaining an anti-condensation and heat-insulating superhydrophobic aerogel coating with a solid content of 45%.

[0089] Example 19: Based on Example 1, the moisture content in S6 was adjusted to make the solid content of the system 78%, while other parameters remained unchanged, thereby obtaining an anti-condensation and heat-insulating superhydrophobic aerogel coating with a solid content of 78%.

[0090] Example 20: Based on Example 1, this example adjusts the hydrophobic nanoridge forming particles in S6 to hydrophobic modified silica sol solid particles with an average particle size of about 10 nm, while keeping other parameters unchanged, thereby obtaining an anti-condensation and heat-insulating superhydrophobic aerogel coating with hydrophobic nanoridge forming particles with a particle size of about 10 nm on the surface.

[0091] Example 21: Based on Example 1, this example adjusts the hydrophobic nanoridge forming particles in S6 to hydrophobic modified silica particles with an average particle size of about 500 nm, while keeping other parameters unchanged, thereby obtaining an anti-condensation and heat-insulating superhydrophobic aerogel coating with hydrophobic nanoridge forming particles with a particle size of about 500 nm on the surface.

[0092] Example 22: Based on Example 1, this example adjusts the amount of hydrophobic fumed silica added in S6 to 1 part, while keeping other parameters unchanged, thereby obtaining an anti-condensation and heat-insulating superhydrophobic aerogel coating with a hydrophobic nanoridge forming particle addition amount of 1 part.

[0093] Example 23: Based on Example 1, this example adjusts the amount of hydrophobic fumed silica added in S6 to 8 parts, while keeping other parameters unchanged, thereby obtaining an anti-condensation and heat-insulating superhydrophobic aerogel coating with 8 parts of hydrophobic nanoridge forming particles.

[0094] Example 24: Based on Example 1, this example adjusts the leveling temperature in S7 to 15℃, the leveling time to 5min, and the pre-curing conditions to 80℃ for 0.5h, while keeping other parameters unchanged, thereby obtaining a dew-point responsive bifacial breathing microcapsules protruding from the coating surface at a height of approximately 10% of their particle size.

[0095] Example 25: Based on Example 1, this example adjusts the leveling temperature in S7 to 35°C, the leveling time to 30 min, and the pre-curing conditions to 40°C for 3 h, while keeping other parameters unchanged. This results in a dew-point responsive, bifacial breathing microcapsules protruding from the coating surface at a height of approximately 45% of their particle size, forming an anti-condensation and heat-insulating superhydrophobic aerogel coating.

[0096] Example 26: This example is based on Example 1, but the amount of the restricted migration type low surface energy chain segment reservoir added is adjusted to 0.5 parts, while other parameters remain unchanged.

[0097] Example 27: This example is based on Example 1, but the amount of the restricted migration type low surface energy chain segment reservoir added is adjusted to 6 parts, while other parameters remain unchanged.

[0098] Example 28: Based on Example 1, this example adjusts the proportion of free polysiloxane to total polysiloxane mass in the confined migration type low surface energy segment reservoir to 0%, while keeping other parameters unchanged.

[0099] Example 29: Based on Example 1, this example adjusts the proportion of free polysiloxane to total polysiloxane mass in the confined migration type low surface energy segment reservoir to 15%, while keeping other parameters unchanged.

[0100] Example 30: This example is based on Example 1, except that the post-curing temperature in step S7 is adjusted to 60°C, while other parameters remain unchanged.

[0101] Example 31: This example is based on Example 1, except that the post-curing temperature in step S7 is adjusted to 110℃, while other parameters remain unchanged.

[0102] Comparative Example 1: This comparative example is based on Example 1, but without the reactive silane grafting in step S1. Only hexadecyltrimethoxysilane is used to hydrophobically modify the silica aerogel, while other parameters remain unchanged.

[0103] Comparative Example 2: This comparative example is based on Example 1, but without the hydrophobic silane grafting in step S1. Instead, γ-glycidoxypropyltrimethoxysilane is used to reactively modify the silica aerogel, while other parameters remain unchanged.

[0104] Comparative Example 3: Based on Example 1, the particle size of the silica aerogel in step S1 was adjusted to 120 μm, while other parameters remained unchanged.

[0105] Comparative Example 4: Based on Example 1, this comparative example replaces the dew point-responsive bifacial breathing microcapsules in S2 with ordinary phase change microcapsules, while keeping other parameters unchanged, thereby obtaining an aerogel coating containing ordinary phase change microcapsules.

[0106] Comparative Example 5: Based on Example 1, this comparative example adjusted the concentration of sodium hydroxide aqueous solution used for alkaline washing in S2 to 0.05 mol / L, the alkaline washing time to 30 min, the volume ratio of ethanol / water mixed solution to 9:1, and the swelling time to 40 min, while keeping other parameters unchanged, thereby obtaining dew point responsive bifacial respiratory microcapsules with an average pore size of approximately 120 nm for semi-through breathing channels.

[0107] Comparative Example 6: Based on Example 1, this comparative example replaces the phase change core material in S2 with a volatile cyclohexane temporary droplet template, while keeping other parameters unchanged, thereby obtaining a hollow bifacial respiratory microcapsule without a phase change core material.

[0108] Comparative Example 7: Based on Example 1, this comparative example adjusts the pH value of the system in S6 to 6.5 while keeping other parameters unchanged, thereby obtaining an anti-condensation and heat-insulating superhydrophobic aerogel coating with a pH value of 6.5.

[0109] Comparative Example 8: Based on Example 1, this comparative example adjusts the amount of rheology modifier added in S6 to 0.05 parts, while keeping other parameters unchanged, thereby obtaining an anti-condensation and heat-insulating superhydrophobic aerogel coating with a wet film viscosity of 1800 mPa·s.

[0110] Comparative Example 9: Based on Example 1, this comparative example adjusts the moisture content in S6 to make the solid content of the system 82%, while keeping other parameters unchanged, thereby obtaining an anti-condensation and heat-insulating superhydrophobic aerogel coating with a solid content of 82%.

[0111] Comparative Example 10: Based on Example 1, this comparative example adjusts the amount of hydrophobic fumed silica added in S6 to 0 parts, while keeping other parameters unchanged, thereby obtaining an aerogel coating without hydrophobic nanoridge forming particles.

[0112] Comparative Example 11: Based on Example 1, this comparative example adjusts the amount of hydrophobic fumed silica added in S6 to 12 parts, while keeping other parameters unchanged, thereby obtaining an anti-condensation and heat-insulating superhydrophobic aerogel coating with 12 parts of hydrophobic nanoridge forming particles.

[0113] Comparative Example 12: Based on Example 1, this comparative example adjusts the leveling temperature in S7 to 35°C, the leveling time to 45 min, and the pre-curing conditions to 40°C for 3 h, while keeping other parameters unchanged, thereby obtaining a dew-point responsive bifacial breathing microcapsules protruding from the coating surface at a height of approximately 60% of their particle size.

[0114] Comparative Example 13: This comparative example is based on Example 1, but without the addition of a restricted migration type low surface energy chain segment reservoir, while keeping other parameters unchanged.

[0115] Comparative Example 14: This comparative example is based on Example 1, but uses 3 parts of free silicone oil to replace the restricted migration type low surface energy segment reservoir, while keeping other parameters unchanged.

[0116] Comparative Example 15: Based on Example 1, this comparative example adjusts the proportion of free polysiloxane in the restricted migration type low surface energy chain segment reservoir to 30% of the total polysiloxane mass, while keeping other parameters unchanged.

[0117] Experiment 1: The coatings obtained in Examples 1-7 and Comparative Examples 1-3 were prepared into coating samples with a thickness of 2.0 mm. The ratio of the interface debonding area was obtained by observing the cross-section after freezing and fracturing the sample. The ratio of the area with continuous black gaps or obvious voids around the aerogel particles in the cross-section to the total observed area around the aerogel particles was taken as the ratio of the interface debonding area. Five regions were taken for each sample and the average value was calculated. The water absorption weight gain rate of the aerogel powder was obtained by weighing the corresponding modified aerogel after placing it in a humid heat environment of 35°C and 95% relative humidity for 72 hours. The interface crack length was obtained by microscopic observation of the coating cross-section after 100 cycles of cold and heat treatment. The increase rate of wet thermal conductivity was calculated based on the dry thermal conductivity and the thermal conductivity after 72 hours of humid heat treatment. Specific data are shown in Table 1.

[0118] Table 1

[0119] Based on Table 1 Figure 2 Part (a) and Figure 2 As can be seen from part (d) in the text, Figure 2 The bifunctional modified aerogel shown in part (a) has both resin-binding groups and low surface energy groups on its surface, so it can form a relatively stable interface bond with resin and silica sol after being dispersed in the coating. Figure 2 In the coating cross-section shown in part (d), the aerogel insulation portion is located in the middle of the coating and together with the anchoring shield portion near the substrate and the condensation repellency portion near the air, forms a continuous structure. Experiment 1 tested the debonding area ratio, interface crack length, and rate of increase of wet thermal conductivity at the cross-section interface, which was used to verify... Figure 2Can the bifunctional modified aerogel shown in part (a) of the paper be used in... Figure 2 The coating structure shown in part (d) maintains good interfacial bonding and water-repellent and heat-insulating effects. The water absorption weight gain rate, interfacial debonding area ratio, interfacial crack length and wet thermal conductivity increase rate of the aerogel powder in Example 1 are all at a low level, indicating that the segmented modification of reactive silane and hydrophobic silane in the preferred embodiment simultaneously improves the bonding state between aerogel and resin and the water-repellent state of aerogel pores.

[0120] Comparative Example 1, without reactive silane grafting, still showed a low water absorption and weight gain rate of the aerogel powder, but the proportion of interfacial debonding area and the length of interfacial cracks increased significantly, indicating that hydrophobic structures alone cannot solve the problem of insufficient bonding between aerogel particles and resin. Comparative Example 2, without hydrophobic silane grafting, showed a relatively low proportion of interfacial debonding area, but the water absorption and weight gain rate of the aerogel powder and the rate of increase in wet thermal conductivity increased significantly, indicating that reactive bonding structures alone cannot prevent condensate from entering the aerogel channels. Comparative Example 3, with adjusted aerogel particle size, showed an increase in the proportion of interfacial debonding area and the length of interfacial cracks, indicating that excessively large particle size would exacerbate local defects inside the coating. The results of Examples 2-7 further illustrate that the synergistic effect can be obtained by changing the particle size and silane grafting conditions, and the parameters of Example 1 resulted in a better balance between interfacial bonding, water repellency, and wet insulation.

[0121] Experiment 2: The coating samples obtained in Examples 1, 8-13, and Comparative Examples 4-6 were fixed on a temperature-controlled metal cold plate. The ambient temperature was set to 30℃ and the relative humidity to 85%. The temperature of the cold plate was reduced from 35℃ to 8℃. The time required for the temperature of the coating near the air to drop below the ambient dew point by 2℃ was recorded. The liquid water intrusion ratio was determined by treating the coating with condensate containing fluorescent dye for 30 minutes. The proportion of microcapsules showing fluorescent signals inside the microcapsule shell was counted by cross-sectional fluorescence observation. The microcapsule breakage ratio was obtained by cross-sectional observation after 50 cycles of condensation at 8℃ / 35℃. The effective exposure ratio was the proportion of the number of microcapsules on or near the coating surface that exhibited bifacial breathing response to the dew point to the total number of microcapsules in the observation area. Specific data are shown in Table 2. Table 2

[0122] Based on Table 2 Figure 2 Part (b) and Figure 3 It can be seen that, Figure 2 The dew point-responsive bifacial respiration microcapsules shown in section (b) are the main subject of Experiment 2. Their internal structure is similar to... Figure 3The phase change core material 1, elastic intermediate layer 2, inorganic nano-roughened shell layer 3, low surface energy side 4, reactive bonding side 5, and semi-through breathing channel 6 are shown in Table 2. The time required to fall below the dew point, the proportion of liquid water intrusion into the shell, the microcapsule breakage rate, and the effective exposed surface rate, tested in Experiment 2, are used to verify the temperature buffering effect of the phase change core material 1, the liquid water barrier effect of the semi-through breathing channel 6, the structural stabilizing effect of the elastic intermediate layer 2 and inorganic nano-roughened shell layer 3, and the role of the low surface energy side 4 and reactive bonding side 5 in the directional distribution and anchoring of the coating surface. Therefore, the data in Table 2 not only reflect the performance of the microcapsule material but also illustrate... Figure 3 The synergistic effect of the multi-layered double-sided structure in the anti-condensation process is shown.

[0123] Example 1 simultaneously exhibits a longer time required to cool below the dew point by 2°C, a lower proportion of liquid water intrusion into the shell, a lower proportion of microcapsule breakage, and a higher proportion of effective surface exposure. Comparative Example 6, lacking a phase change core material, shows a significantly shorter time for the coating to cool below the dew point, indicating that the phase change core material directly affects the temperature change process on the air-facing side of the coating. Comparative Example 5, by adjusting the pore size of the breathing channel to 120 nm, while still maintaining temperature buffering capacity, shows a significantly increased proportion of liquid water intrusion, indicating that excessively large pore sizes make it easier for condensed liquid water to enter the microcapsule shell. Comparative Example 4, using ordinary phase change microcapsules, although able to delay temperature decrease, shows a significant increase in liquid water intrusion. The intrusion rate, microcapsule breakage rate, and effective surface exposure rate were all significantly worse than in Example 1, indicating that ordinary phase change microcapsules cannot replace the combined structure of phase change core material, semi-through breathing channel, and double-sided outer surface in this invention. As can be seen from Examples 8-13, the particle size, pore size, and phase change temperature synergistically solved the technical problems of condensate entering the coating after nucleation inside the micro-nano structure, and ordinary phase change microcapsules can only provide heat buffering but cannot control the entry of liquid water. However, in Example 1, when the particle size is about 22 μm, the pore size is about 30 nm, and the phase change temperature is about 28 °C, the coordination between temperature buffering, liquid water entry inhibition, and surface exposure is better.

[0124] Experiment 3: The wet films obtained from Examples 1, 14-19, and Comparative Examples 7-9 were coated on the same carbon steel plate surface, and dry films were prepared according to the same leveling, pre-curing, and post-curing regimes. The ratio of the number of microcapsules in the one-third thickness of the coating closest to the air to the average number of microcapsules in the entire thickness was observed and statistically analyzed using cross-sectional microscopy, and this ratio was used as the enrichment factor of surface microcapsules. The agglomeration area ratio was obtained through surface image analysis of the coating. The ratio of microcapsule protrusion height to particle size was determined by a combination of three-dimensional profile testing and cross-sectional observation. The dry film thickness deviation was the ratio of the standard deviation of the thickness at 10 locations of the same sample to the average thickness. Specific data are shown in Table 3.

[0125] Table 3

[0126] As shown in Table 3, Example 1 achieved a good balance between the enrichment factor of surface microcapsules, the proportion of agglomeration area, the proportion of protrusion height to particle size, and the dry film thickness deviation. In Comparative Example 7, the pH value was adjusted, resulting in a decrease in the enrichment factor of surface microcapsules and an increase in the proportion of agglomeration area, indicating that the pH value of the system affects the binding state between silica sol, microcapsule shell, and resin. In Comparative Example 8, the wet film viscosity was too low. Although the microcapsule enrichment factor was relatively high, the proportion of agglomeration area and the proportion of protrusion height to particle size were too large, indicating that excessively low viscosity would cause microcapsules to float excessively and destroy surface uniformity. In Comparative Example 9, the solid content was too high, which hindered microcapsule migration, resulted in a significantly insufficient proportion of protrusion height to particle size, and increased the dry film thickness deviation, indicating that excessively high solid content would affect the formation of the surface anti-condensation structure. Examples 14-19 show that adjusting the pH value, wet film viscosity, and solid content can all form an enriched structure of microcapsules near the air side. Among them, the parameters of Example 1 enabled the microcapsules to be effectively enriched without significant agglomeration or excessive protrusion.

[0127] Experiment 4: The coated samples obtained from Examples 1, 20-25, and Comparative Examples 10-12 were placed in a constant temperature and humidity environment of 30℃ and 85% relative humidity. The back of the samples was cooled to 8℃ via a cold plate and maintained for 20 minutes. The desorption force of the droplet three-phase contact line was obtained by using a micro-force sensor to push a condensed droplet with a diameter of approximately 1.0 mm and recording the maximum resistance when the droplet began to move. The critical desorption volume of the condensed droplet was obtained by continuously observing the droplet growth process and recording the volume when the droplet began to slide or roll off. The number of residual droplets per unit area was the number of droplets with a diameter greater than 100 μm that remained on the surface per square centimeter after 20 minutes of condensation. The roll-off angle after condensation cycles was the roll-off angle measured using a 10 μL water droplet after 50 condensation cycles. Specific data are shown in Table 4.

[0128] Table 4

[0129] Based on Table 4 Figure 2 Part (c) and Figure 2 As can be seen from part (d) in the text, Figure 2 The hydrophobic nanoridge-forming particles shown in section (c) are used to construct nanoscale protrusions around dew-point responsive bifacial respiratory microcapsules. Figure 2 In the coating cross-section shown in part (d), the microcapsules form partially exposed micron-scale micro-protrusions on the side closest to the air. Together, these micro-protrusions and nano-ridges constitute a condensation rejection structure. In Experiment 4, the desorption force of the three-phase contact line, the critical desorption volume of the condensed droplets, the number of residual droplets per unit area, and the roll-off angle after condensation cycle were measured to evaluate the results. Figure 2 Part (c) and Figure 2Whether the structure shown in part (d) can promote the transformation of condensed droplets from a state of overall pinning to one of edge depinning, local peeling, and overall slippage is further demonstrated by the data in Table 4. This indicates a synergistic relationship between the hydrophobic nanoridge-forming particles and the enriched structure on the surface of the microcapsule, rather than relying solely on low surface energy materials to achieve the initial superhydrophobic effect. Example 1 exhibits the lowest three-phase contact line desorption force and critical desorption volume, fewer residual droplets, and a lower roll-off angle after 50 condensations, indicating that the microcapsule protrusion height combined with the nanoridge structure in Example 1 promotes edge desorption of condensed droplets. In Comparative Example 10, without the addition of hydrophobic nanoridge-forming particles, the droplet desorption force and critical desorption volume significantly increase, indicating that only micron-scale... The micro-convex structure is insufficient to reduce the pinning of the three-phase contact line; in Comparative Example 11, the amount of nano-ridges added was too high, and the number of residual droplets and the roll-off angle increased instead, indicating that excessive nanoparticles are prone to forming particle accumulation and condensation nucleation sites, and the anti-condensation performance cannot be improved simply by increasing the number of nanoparticles; in Comparative Example 12, the microcapsule protrusion height was too high, and the desorption performance of condensed droplets was not further improved, and the number of residual droplets increased, indicating that excessive protrusion of the micro-convex structure will lead to a decrease in surface durability and uniformity; as can be seen from Examples 20-25, changing the nano-ridge particle size, the amount added, and the protrusion height of the microcapsules can all achieve droplet edge peeling effect, but the parameters of Example 1 resulted in the lowest desorption force of the three-phase contact line, showing a better synergistic effect.

[0130] Example 5: The coated samples obtained from Examples 1, 26-31, and Comparative Examples 13-15 were first aged in an environment of 60°C and 95% relative humidity for 168 hours, then wiped 100 times with a clean cloth under a specified load, and subsequently heat-treated at 80°C for 1 hour. The recovery rate of the relative content of silicon on the surface was calculated by the change in the Si / C atomic ratio on the surface after aging and wiping and after heat treatment. The change rate of water droplet adhesion work was calculated by the contact angle test. The amount of siloxane precipitation was obtained by measuring the mass of the extract after wiping the sample surface with n-hexane. The adhesion retention rate after wet heat was calculated by the adhesion test results of the pull-off method before and after wet heat treatment. Specific data are shown in Table 5.

[0131] Table 5

[0132] Based on Table 5 Figure 3 It can be seen that, Figure 3The low surface energy side 4, together with the reservoir of confined migration-type low surface energy segments, determines the hydrophobic recovery ability of the coating surface. The reactive bonding side 5 forms a bond with the resin, silica sol, or microcapsule shell, thereby restricting the disordered migration of low surface energy segments. Experiment 5 tests the relative recovery rate of surface silicon element content, the reduction rate of water droplet adhesion work, the amount of siloxane precipitation, and the adhesion retention rate after humid heat. These tests are used to verify whether low surface energy segments can reorient themselves to the coating surface after aging and wiping, without precipitating out in large quantities and destroying adhesion like free silicone oil. Figure 3 The bifacial structure of the low surface energy side 4 and the reaction-bonding side 5, together with the confined migration type low surface energy chain reservoir, supports the superhydrophobic retention effect of the coating after humid heat aging and slight wear.

[0133] Example 1 showed a good balance between the recovery rate of relative silicon content, the reduction rate of water droplet adhesion work, the amount of siloxane precipitation, and the adhesion retention rate after humid heat. Comparative Example 13, without the addition of a confined migration type low surface energy segment reservoir, showed significantly lower recovery rates of relative silicon content and water droplet adhesion work reduction, indicating a lack of low surface energy segment replenishment after aging and wiping. Comparative Example 14, using free silicone oil instead of the confined migration type low surface energy segment reservoir, showed a higher recovery rate of relative silicon content, but significantly higher siloxane precipitation. The increase in free silicone oil and the significant decrease in adhesion retention after humid heat indicate that the migration of free silicone oil is unrestricted and will compromise the long-term stability of the coating. In Comparative Example 15, the proportion of free polysiloxane was too high, resulting in a high amount of precipitation and a low adhesion retention, indicating that the migratory portion of the low surface energy chain segments must be restricted. As can be seen from Examples 26-31, the amount of reservoir addition, the proportion of free polysiloxane, and the post-curing temperature can all work together to achieve a certain degree of hydrophobic recovery, while the parameters of Example 1 can achieve a better balance between low surface energy recovery and low precipitation.

[0134] Therefore, the above experiments show that Experiment 1 demonstrates that segmental modification of aerogel with reactive and hydrophobic silanes can simultaneously reduce interfacial defects between the aerogel and resin and the water absorption tendency of the aerogel pores, thus maintaining a low thermal conductivity of the coating under humid and hot conditions; Experiment 2 demonstrates that the phase change core material, semi-through breathing channels, and double-sided outer surface of the dew point-responsive bifacial breathing microcapsule work together to enable the coating to have temperature buffering, liquid water ingress inhibition, and effective surface exposure capabilities when approaching the dew point; Experiment 3 demonstrates that pH value and wet film... The combined regulation of viscosity and solid content enables microcapsules to form a stable distribution on the air-facing side of the coating, avoiding random dispersion, excessive floating, or complete encapsulation. Experiment 4 shows that the elastic micro-convex structure formed by the dew-point responsive bifacial breathing microcapsules and the nano-protrusions formed by the hydrophobic nano-ridge forming particles jointly reduce the desorption force of the three-phase contact line of condensate droplets and promote the peeling off of the condensate droplet edges. Experiment 5 shows that the confined migration type low surface energy chain segment reservoir can replenish the low surface energy after heat treatment, while avoiding the precipitation of a large amount of free silicone oil and the decrease in adhesion.

[0135] Based on the preferred embodiments of the present invention described above, those skilled in the art can make various changes and modifications without departing from the inventive concept. The technical scope of this invention is not limited to the contents of the specification, but must be determined according to the scope of the claims.

Claims

1. A method for preparing an anti-condensation and heat-insulating superhydrophobic aerogel coating, characterized in that, Includes the following steps: S1: Silica aerogel is modified in stages with reactive silane and hydrophobic silane in an alcohol-water mixed medium to obtain a bifunctional modified aerogel containing both resin-binding groups and low surface energy groups. S2: The phase change core material is emulsified into droplets, and an elastic intermediate layer, an inorganic nano-rough shell, and a bifacial outer surface with semi-through breathing channels are sequentially formed on the outside of the droplets to obtain dew point responsive bifacial breathing microcapsules. S3: Confined grafting of polysiloxanes with terminal hydroxyl, terminal epoxy, or terminal alkoxy groups to some bifunctional modified aerogels, silica sols, or dew-point responsive bifacial breathing microcapsules yields confined migration type low surface energy segment reservoirs. S4: A base slurry is obtained by mixing waterborne silicone-modified film-forming resin, sheet-like shielding filler, flame-retardant filler, dispersant, defoamer, rheology modifier, film-forming aid, and water. S5: Add the bifunctional modified aerogel, hollow heat-insulating microspheres and part of silica sol obtained in S1 to the base slurry obtained in S4, and mix them under low shear conditions to obtain aerogel heat-insulating slurry. S6: Add the dew-point responsive bifacial breathing microcapsules, hydrophobic nanoridge forming particles, and the confined migration type low surface energy chain segment reservoir obtained in S2 to the aerogel insulation slurry obtained in S5, adjust the pH value, wet film viscosity and solid content of the system, and obtain an anti-condensation heat-insulating superhydrophobic aerogel coating. S7: The anti-condensation and heat-insulating superhydrophobic aerogel coating obtained in S6 is applied to the outer surface of industrial thermal equipment, and leveling, pre-curing and post-curing are performed in sequence. This allows the dew point-responsive bifacial breathing microcapsules to accumulate on the side of the coating closest to the air, and together with the hydrophobic nanoridge particles and the confined migration low surface energy chain segment reservoir, they form a condensate droplet edge peeling structure, thus obtaining the anti-condensation and heat-insulating superhydrophobic aerogel coating. The semi-through breathing channels are not straight holes that extend directly from the outer surface of the microcapsule to the interior of the phase change core material, but rather tortuous or incompletely penetrating fine channels formed in the shell. The bifacial outer surface includes a low surface energy side and a reactive bonding side. The low surface energy side is used to form a water-repellent surface facing the air interface, and the reactive bonding side is used to bond with the resin and inorganic components inside the coating. The confined grafting involves fixing one end of the polysiloxane chain segment near the shell of the bifunctional modified aerogel, silica sol, or dew-point responsive bifacial breathing microcapsule, so that the polysiloxane chain segment can only be oriented within a certain range and cannot flow in large quantities, while the other end retains the orientation capability of the low surface energy siloxane chain segment to form the confined migration type low surface energy chain segment reservoir. The hydrophobic nanoridge forming particles are particles distributed around the microcapsule and on the coating surface to form nanoscale protrusions. The nanoscale protrusions are discontinuous nanoprotrusions or sheet-like edge structures.

2. The preparation method of the anti-condensation and heat-insulating superhydrophobic aerogel coating according to claim 1, characterized in that: In S1, the silica aerogel has a particle size of 5-80 μm, a pore size of 10-100 nm, and an apparent density of 0.04-0.20 g / cm³. Reactive silanes include one or more of γ-glycidoxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane, methacryloyloxypropyltrimethoxysilane, or vinyltriethoxysilane; Hydrophobic silanes include one or more of octyltriethoxysilane, dodecyltrimethoxysilane, hexadecyltrimethoxysilane, methyltrimethoxysilane, or polydimethylsiloxane; The segmented modification involves first grafting reactive silanes at a pH of 4.0-6.0 and a temperature of 35-65℃ for 0.5-3 hours, and then grafting hydrophobic silanes at a pH of 7.0-9.5 and a temperature of 40-75℃ for 0.5-4 hours.

3. The preparation method of the anti-condensation and heat-insulating superhydrophobic aerogel coating according to claim 1, characterized in that: In S2, the phase change core material includes one or more of C14-C22 n-alkanes, fatty acid esters, low-melting-point silicone wax or paraffin, and the phase change temperature of the phase change core material is 15-42℃. The dew-point responsive bifacial respiratory microcapsules have a particle size of 5-50 μm, a shell thickness of 0.2-3.0 μm, and a semi-perforated breathing channel pore size of 5-80 nm. The elastic interlayer includes one or more of polyurea, polyurethane, polysiloxane, or acrylate elastomer; Inorganic nano-rough shells include one or more of silica, silica sol condensate, silsesquioxane, nano-alumina, or sheet silicates. The bifacial outer surface includes a low surface energy side and a reactive bonding side. The low surface energy side contains one or more of polydimethylsiloxane segments, C8-C18 alkylsiloxane segments, or phenylsiloxane segments, while the reactive bonding side contains one or more of hydroxyl, amino, epoxy, carboxyl, or alkenyl groups.

4. The preparation method of the anti-condensation and heat-insulating superhydrophobic aerogel coating according to claim 1, characterized in that: In the S3, in the confined migration type low surface energy segment reservoir, one end of the polysiloxane segment forms a silicon-oxygen bond, hydrogen bond or covalent bond with the shell of bifunctional modified aerogel, silica sol or dew point responsive bifacial breathing microcapsule, and the other end is a low surface energy segment that can be reoriented to the coating surface after heat treatment at 40-100℃. In confined migration type low surface energy chain segment storage, the mass of free polysiloxane accounts for 0-15% of the total polysiloxane mass.

5. The preparation method of the anti-condensation and heat-insulating superhydrophobic aerogel coating according to claim 1, characterized in that: In S4 and S5, the waterborne silicone-modified film-forming resin includes one or more of the following: waterborne silicone-modified polyurethane emulsion, waterborne silicone-acrylic emulsion, waterborne siloxane-modified polyurethane-acrylic composite emulsion, or phosphate ester-modified acrylic emulsion. The sheet-like shielding filler includes one or more of mica, sheet-like silicate, hexagonal boron nitride, or sheet-like ceramic filler; Flame-retardant fillers include one or more of aluminum hydroxide, magnesium hydroxide, expanded graphite, ammonium polyphosphate, melamine polyphosphate, or zinc borate; Hollow insulating microspheres include one or more of hollow glass microspheres, hollow ceramic microspheres, closed-cell expanded microspheres, or hollow silicate microspheres, with a particle size of 10-120 μm and an apparent density of 0.10-0.60 g / cm³. The low shear conditions are a rotation speed of 100-800 r / min and a mixing time of 5-40 min.

6. The method for preparing an anti-condensation and heat-insulating superhydrophobic aerogel coating according to claim 1, characterized in that: In S6, the hydrophobic nanoridge forming particles include one or more of chain-like nano silica, fumed silica, hydrophobically modified silica sol, sheet-like nano silicates, nano alumina, or nano sericite, with a particle size or thickness of 10-500 nm. In S6, the pH value of the system is adjusted to 7.5-9.5, the wet film viscosity is adjusted to 3000-12000 mPa·s, and the solid content is adjusted to 45-78%.

7. The preparation method of the anti-condensation and heat-insulating superhydrophobic aerogel coating according to claim 1, characterized in that: In step S7, the leveling temperature is 15-35℃ and the time is 5-30 min; The pre-curing temperature is 40-80℃ and the time is 0.5-3h; the post-curing temperature is 60-110℃ and the time is 1-8h; the dry film thickness of the resulting anti-condensation and heat-insulating superhydrophobic aerogel coating is 0.5-5.0mm. The height of the dew-point responsive bifacial breathing microcapsules protruding from the coating surface is 10-45% of their particle size, and the spacing between adjacent dew-point responsive bifacial breathing microcapsules is 5-80 μm.

8. The preparation method of the anti-condensation and heat-insulating superhydrophobic aerogel coating according to claim 1, characterized in that: By weight, the anti-condensation and heat-insulating superhydrophobic aerogel coating comprises 18-45 parts of waterborne silicone-modified film-forming resin, 8-32 parts of bifunctional modified aerogel, 4-20 parts of hollow heat-insulating microspheres, 4-18 parts of dew-point responsive bifacial breathing microcapsules, 1-8 parts of hydrophobic nanoridge-forming particles, 2-14 parts of silica sol, 1-10 parts of sheet-like shielding filler, 5-25 parts of flame-retardant filler, 0.5-6 parts of confined migration type low surface energy chain segment reservoir, 0.2-2 parts of dispersant, 0.1-1 parts of defoamer, 0.2-3 parts of rheology modifier, 0.5-5 parts of film-forming aid, and 20-70 parts of water.

9. A superhydrophobic aerogel coating with anti-condensation and thermal insulation properties, characterized in that: The coating is prepared by the preparation method according to any one of claims 1-8; the coating formed after curing includes an anchoring shielding part near the substrate, an aerogel heat insulation part in the middle and a condensation repellent part near the air; the water contact angle of the coating is 150-168° and the roll-off angle is 1-10°.

10. The application of an anti-condensation and heat-insulating superhydrophobic aerogel coating in industrial thermal equipment, characterized in that: The anti-condensation and heat-insulating superhydrophobic aerogel coating is the coating described in claim 9; the industrial thermal equipment includes a low-temperature storage tank, a chilled water pipeline, a heat exchanger shell, a reactor jacket outer wall, a steam pipeline shutdown cooling section, a compressed air aftercooling pipeline, a heat pump equipment shell, and a cooling unit shell.

Citation Information

Patent Citations

  • Seamless constant-temperature moisture-absorbing and heating fabric containing phase-change microcapsules and preparation method of seamless constant-temperature moisture-absorbing and heating fabric

    CN121802613A

  • Anti-condensation anti-icing self-cleaning coating for high-voltage transmission line and preparation method of anti-condensation anti-icing self-cleaning coating

    CN121950178A